Relationship of Knowledge, Motivation and Role of PMO with the Drop Out of Tuberculosis Treatment in Mahakam Ulu District - Edi Hartono; Parellangi Parellangi; Hesti Hesti (MultiTech Publisher, 2023)
It is estimated that there are 1,000,000 new TB cases per year (399 per 100,000 inhabitants) with 100,000 deaths per year (41 per 100.000 population) in Indonesia.Instead, if the treatment is not regular and the combination of OAT is incomplete, it will result in treatment failure and result in Mycrobacterium Tuberculosis becoming immune, causing the occurrence of MDR cases. (Multidrug Resistance). This research aims to find out the relationship of knowledge, motivation and role of PMO with the case of TB treatment drop out in Mahakam Ulu District. This research uses analytical research design with cross-sectional approach. The sample was selected by consecutive sampling. There is a connection between knowledge, motivation, and the role of the PMO with the TB drop out incident.